Relevance of Legal Capacity as Legitimate Terms of Agreement of Saving for Child in the Bank - Muhammad As Ari; Moch Nadjib Imanullah; Setiono Setiono (The Indonesian Journal of International Clinical Legal Education, 2019)
Indonesia is law state such as inserted in constitutional 1945. Legitimation Indonesia as law state have the impact that all attitude have to relevance by law. Similarly act such as saving in the bank. The law Number 10 of 1998 concerning change of the law Number 7 of 1992 concerning the banking stated the definition account saving as follows: “account saving is savings who can be taken accord agreement of parties only, but it can’t be taken with check, billyet, giro ect”. The definition of account saving upon explain implicitly that terms of agreement of saving surrender parties (pay attention of sentence “according specialist term by parties”). The sentence upon is norm blanked should facilitate the child for saving independent according of the best interest of the child principle. But the banking decided use the general law about legal capacity one forbidden the child saving independent. The law one forbidden the child saving independent is going to give impact such as is blocked protective of law to interest child are for live, grow and develop for prepare the future their selves. Salving independent by the child are growth and development psychologically. According a research by Child and Youth Finance International said “the human one saving since child period is better than the human don’t save since child period. It’s mean attitude saving is going to become the child find best growth and the best psychological development.